PEMBUATAN DAN KARAKTERISASI EKSTRAK AIR HERBA MENIRAN (Phyllanthus niruri Linn) - erniza - pratiwi (Jurnal Penelitian Farmasi Indonesia, 2014)
Extraction by percolation method of meniran herb and its characterization has been done. The extraction was carried out by using boiled distilledwater and the resulting percolate was concentrated by using rotary evaporator until the remainni g volume was equivalent to theweight of meniranherbs extracted. The aquaeous extract of meniran herbs was further studied for its characters in terms of non specific, specific and chemical content.It was found that the extract has values of 93.80% ± 4.27 % for loss on drying, 4.78% ± 0.27% for residu of ignition, 0.71% ± 0.18% for insolubleacid ash value and 1.07 for specific gravity parameters. Theinthlayer chromatogram pattern save three spots in which one of them indicated thepresence of quercetin since it has the same Rf value (0.30) to the standard solution of quercetin applied.